Disability and Healing in Greek and Roman Myth. Laes, Christian. Cambridge University Press, Cambridge, 2024, 82 pp. ISBN: 978-1-009-49466-3 - Méndez Santiago, Borja (Antigüedad y Cristianismo, 2024)
Reseña de Christian Laes (2024), Disability and Healing in Greek and Roman Myth